Pro bono - Perry, Thomas, 1947- (The Mysterious Press, 2025)
"Los Angeles attorney Charles Warren is helping a young widow find her late husband's missing money when he recognizes a con job that targeted his widowed mother years before, and he quickly becomes entangled in the web of fraud, betrayal, and criminals surrounding the theft"--